Strategic leadership of Information Systems in The Development of The Digital Economy: Kepemimpinan Strategis Sistem Informasi dalam Pengembangan Ekonomi Digital - Salim , Moamin Mazin; Saeed , Yasir Jihad; Ahmed , Dahlia Abdulhussein; Ibrahim, Mustafa Ali (Universitas Muhammadiyah Sidoarjo, 2024)
The essay explores contemporary trends in the economic transformation of nations driven by digital technology. It provides an overview of key technology paradigms shaping economic growth and outlines the primary characteristics of the digital economy, such as shifts in production resources, evolving IT cycles, and the importance of networked models emphasizing connectivity, self-sufficiency, and autonomy. The economic landscape of the digital era is analyzed, with a focus on institutional frameworks, relational norms, and the prerequisites for adapting education systems to meet digital economy demands. The role of knowledge in societal evolution and its interaction with institutional environments and information domains is highlighted, alongside tools for information processing and protection. The essay presents the results of the Digital Economy Index (DEI) and its components, providing insights into the status of digital transformation. Based on these findings, proposals are formulated to advance the digital economy in the Republic of Iraq, addressing challenges and leveraging opportunities identified through statistical analysis and provided data. Highlights: Digital technology reshapes economies and drives development trends. Focus on connectivity, autonomy, and knowledge transformation in digital era. Proposals enhance Iraq's digital economy based on DEI analysis. Keywords: information age, digital economy, knowledge economy, technological order, institutional environment, digital economy index